“Prevalencia de leucemia felina (vilef) en los felinos domésticos (felis silvestris catus) en la parroquia San Miguel del cantón Salcedo, provincia de Cotopaxi” - Arboleda Lozada, Anabelle Stephanie (2023)
Feline leukemia (ViLeF) presents a high morbidity and mortality, affecting cats all over the world with a symptomatology wide range. This infectious disease is more predisposing in the young cat stage. The research aim was to determine the feline leukemia prevalence in domestic cats (Felis silvestris catus) in the San Migue parish, through the rapid immunochromatography diagnostic kits application. It worked a with a 107 cats base sample with a confidence level 92%, the same ones, what were distributed for the 40 neighborhoods, which comprise the urban part from Salcedo canton. It was applied a survey, where it was determined the associated risk factors with the feline leukemia prevalence, as well as it was used the Microsoft Excel 2016 software and the "Chi square" statistical test for establishing their relationship. As a result, it was got 15 cats positive for ViLeF, meanings a prevalence 14.02%. Likewise, it was observed, what there is no significant statistical difference against all risk factors (age, sex, reproductive status, access to the exterior, living with more cats and health status). Finally, it was made an epidemiological map, where it could locate the neighborhoods with positive cases in the San Miguel parish.